Dental resin material, method for producing same, and dental molded body
By introducing nanocellulose three-dimensional fabrics into dental resin materials, the problem of insufficient mechanical properties of traditional dental restoration materials is solved, and higher strength and wear resistance are achieved, the repair effect is improved and the risk of bacterial growth is reduced.
Patent Information
- Application Number
- CN202411937564.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional dental restorative materials have insufficient mechanical properties, insufficient strength and wear resistance, which leads to poor performance in high-demand dental applications and are prone to wear and deformation, affecting the repair effect and may breed bacteria and endangering oral health.
Using a dental resin material containing a resin polymer and a nanocellulose three-dimensional fabric, the strength and wear resistance of the material are enhanced by dispersing the nanocellulose three-dimensional fabric in the resin polymer.
It significantly improves the strength and wear resistance of dental resin materials, enables them to withstand greater chewing pressure, reduces wear and deformation, maintains repair effects, and reduces the risk of bacterial growth, and improves the defects of traditional hard resin materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of dental materials, and in particular to a dental resin material and a preparation method thereof, and a dental molded body. Background Art
[0002] With the continuous development of dental technology, the performance requirements for dental materials are getting higher and higher. Traditional porcelain materials are brittle and easy to break when subjected to large external forces. For example, porcelain collapse may occur when chewing hard objects. Its processing is complicated and requires multiple steps such as high-temperature firing. It not only consumes a lot of energy, but also is prone to dimensional deviations, surface defects and other problems during the processing, resulting in increased restoration costs and limited restoration effects. Although hard resin materials are relatively easy to process, their mechanical properties such as strength and wear resistance are insufficient; during long-term use, due to chewing friction in the mouth and the chemical effects of food and saliva, hard resin restorations are prone to wear and deformation, and the surface roughness increases, which not only affects the restoration effect, but may also breed bacteria and endanger oral health. These defects limit the application of traditional dental restorative materials in a wider range of scenarios, and it is difficult to meet the high performance and multi-functional requirements of modern dental restorations. Summary of the invention
[0003] Based on this, the present application provides a dental resin material and a preparation method thereof, and a dental molded body, wherein the dental resin material has improved mechanical properties.
[0004] A first aspect of the present application provides a dental resin material, comprising a resin polymer and a three-dimensional nanocellulose fabric, wherein the three-dimensional nanocellulose fabric is dispersed in the resin polymer.
[0005] In some embodiments of the present application, one or more of the following conditions are met:
[0006] (1) The mass percentage of the resin polymer in the dental resin material is 10% to 25%, and can be 15% to 25%;
[0007] (2) The mass percentage of the nanocellulose three-dimensional fabric in the dental resin material is 10% to 35%, and can be 20% to 25%;
[0008] (3) The length of the nanocellulose three-dimensional fabric is 15 mm to 150 mm, the width is 15 mm to 150 mm, and the thickness is 10 mm to 25 mm.
[0009] In some embodiments of the present application, the three-dimensional nanocellulose fabric comprises a mesh structure formed by interweaving warp nanocellulose fibers and weft nanocellulose fibers;
[0010] Optionally, the diameters of the warp nanocellulose fibers and the weft nanocellulose fibers are each independently 1 μm to 10 μm;
[0011] Optionally, the spacing between two adjacent warp nanocellulose fibers is 20 μm to 40 μm;
[0012] Optionally, the spacing between two adjacent weft nanocellulose fibers is 20 μm to 40 μm;
[0013] Optionally, the angle between any two intersecting warp nanocellulose fibers and the weft nanocellulose fibers is 4° to 6°.
[0014] In some embodiments of the present application, the polymerized monomers of the resin polymer include one or more of methyl methacrylate, bisphenol A glycidyl methacrylate, triethylene glycol dimethacrylate and urethane dimethacrylate.
[0015] In some embodiments of the present application, the dental resin material further comprises an inorganic filler and / or an additive;
[0016] Optionally, the mass percentage of the inorganic filler in the dental resin material is 20% to 40%;
[0017] Optionally, the mass percentage of the additive in the dental resin material is less than or equal to 5%.
[0018] The second aspect of the present application provides a method for preparing a dental resin material, comprising:
[0019] The nanocellulose three-dimensional fabric is immersed in a mixed solution, wherein the mixed solution contains polymerization monomers of a resin polymer and an initiator;
[0020] The nanocellulose three-dimensional fabric after the soaking treatment is hot-pressed to make the polymerization monomer in situ polymerize on the nanocellulose three-dimensional fabric to form a resin polymer, and the nanocellulose three-dimensional fabric is dispersed in the resin polymer to prepare a dental resin material.
[0021] In some embodiments of the present application, one or more of the following conditions are met:
[0022] (1) The immersion temperature is 40°C to 60°C;
[0023] (2) The soaking time is 0.5h~2h;
[0024] (3) The negative pressure of the environment during the immersion treatment is 0.1 MPa to 1.3 MPa.
[0025] In some embodiments of the present application, the mixed solution further comprises an inorganic filler and / or an additive;
[0026] Optionally, based on the total mass of the polymerization monomer, the initiator, the nanocellulose three-dimensional fabric, the inorganic filler and the additive, the mass percentage of the polymerization monomer is 19% to 30%, the mass percentage of the initiator is 0.5% to 3%, the mass percentage of the nanocellulose three-dimensional fabric is 10% to 30%, the mass percentage of the inorganic filler is 20% to 40%, and the mass percentage of the additive is less than or equal to 5%.
[0027] In some embodiments of the present application, one or more of the following conditions are met:
[0028] (1) The temperature of the hot pressing is 90°C to 170°C;
[0029] (2) The hot pressing pressure is 10MPa~170MPa;
[0030] (3) The heat preservation time of the hot pressing is 1h~4h.
[0031] The third aspect of the present application provides a dental molded body, comprising the dental resin material described in the first aspect of the present application or the dental resin material prepared by the preparation method described in the second aspect of the present application.
[0032] The dental resin material provided in the present application is composited with nanocellulose three-dimensional fabric into the resin polymer. The addition of the nanocellulose three-dimensional fabric can effectively improve the strength and wear resistance of the resin material. DETAILED DESCRIPTION
[0033] In order to facilitate understanding of the present application, the present application will be described more comprehensively below. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0034] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are for the purpose of describing specific embodiments only and are not intended to limit this application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" are inclusive of the number, and the meaning of "multiple" in "one or more" is more than two.
[0036] Herein, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values within the numerical interval is considered to be continuous and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when a numerical interval only refers to integers within the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.
[0037] In this article, if there are multiple steps involved in the method flow, unless there is a clear different description in this article, there is no strict order restriction for the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.
[0038] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0039] At present, in actual dental applications, for some special parts or high-demand restoration scenarios, higher mechanical properties may be required to ensure the long-term stability and durability of the restoration. However, traditional dental resins have obvious defects in mechanical properties, such as insufficient strength and hardness, which makes them perform poorly in these high-demand dental applications. In view of this, the present application proposes the following technical solution.
[0040] In a first aspect, the present application provides a dental resin material, comprising a resin polymer and a three-dimensional nanocellulose fabric, wherein the three-dimensional nanocellulose fabric is dispersed in the resin polymer.
[0041] The dental resin material provided by the present application is a composite of nanocellulose three-dimensional fabrics with the resin polymer. The addition of the nanocellulose three-dimensional fabric can effectively improve the strength of the resin material, so that it can withstand greater chewing pressure, overcome the problem of insufficient strength and hardness of traditional dental resins, perform better in high-demand scenarios such as posterior tooth repair, and reduce the risk of restoration breakage. At the same time, it can also significantly enhance the wear resistance of the resin material. In the long-term oral environment, it can effectively resist chewing friction and the chemical effects of food and saliva, reduce wear, deformation, and increased surface roughness, maintain the repair effect, and reduce the risk of bacteria breeding due to surface roughness that endangers oral health, improving the defect of insufficient wear resistance of traditional hard resin materials.
[0042] In some embodiments, the mass percentage of the resin polymer in the dental resin material is 10% to 25%, and can be 15% to 25%. This helps to better balance the applicability of the dental resin material in dental restorations, as well as its own strength and wear resistance.
[0043] In some embodiments, the mass percentage of the nanocellulose three-dimensional fabric in the dental resin material is 10% to 35%. For example, the mass percentage can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 35% or within the range of any of the above values; it can be 15% to 25%. In this way, the strength and wear resistance of the dental resin material can be further improved.
[0044] As an example, the mass percentage of nanocellulose three-dimensional fabric in dental resin material can be tested by the following method: weigh a certain amount of dental resin material sample, recorded as m1. Then remove the resin by a suitable method, such as high-temperature burning method, burning at a certain temperature (such as 500℃~600℃) in a muffle furnace for a period of time to completely decompose or volatilize the resin, and the remaining is the nanocellulose three-dimensional fabric, and its mass is weighed as m2. Then the mass percentage of nanocellulose three-dimensional fabric in the resin material can be calculated by the formula: w=(m2 / m1)×100%.
[0045] In some embodiments, the length of the nanocellulose three-dimensional fabric is 15 mm to 150 mm, and can be optionally 20 mm to 100 mm; the width is 15 mm to 150 mm, and can be optionally 20 mm to 100 mm; the thickness is 10 mm to 25 mm, and can be optionally 10 mm to 20 mm.
[0046] In some embodiments, the three-dimensional nanocellulose fabric comprises a mesh structure formed by interweaving warp nanocellulose fibers and weft nanocellulose fibers.
[0047] In some embodiments, the diameters of the warp nanocellulose fibers and the weft nanocellulose fibers are independently 1 μm to 10 μm, and may be 4 μm to 7 μm. In this way, the nanocellulose three-dimensional fabric can have higher strength.
[0048] In some embodiments, the spacing between two adjacent warp nanocellulose fibers is 20 μm to 40 μm, and can be 10 μm to 15 μm. In this way, the nanocellulose three-dimensional fabric can have higher strength.
[0049] In some embodiments, the spacing between two adjacent weft nanocellulose fibers is 20 μm to 40 μm, and can be 10 μm to 15 micrometers. In this way, the nanocellulose three-dimensional fabric can have higher strength.
[0050] In some embodiments, the angle between any two intersecting warp nanocellulose fibers and the weft nanocellulose fibers is 4° to 6°. In this way, the nanocellulose three-dimensional fabric can have higher strength.
[0051] In some embodiments, the polymerizable monomers of the resin polymer include one or more of methyl methacrylate (MMA), bisphenol A glycidyl methacrylate (BIS-GMA), triethylene glycol dimethacrylate (TEGDMA) and urethane dimethacrylate (UDMA). These polymerizable monomers have good biocompatibility and polymerizability, can form a strong polymer network, and make the resin polymer have good mechanical properties.
[0052] In some embodiments, the dental resin material further comprises an inorganic filler and / or an additive.
[0053] In some embodiments, the mass percentage of the inorganic filler in the dental resin material is 20% to 40%.
[0054] In some embodiments, the mass percentage of the additive in the dental resin material is less than or equal to 5%.
[0055] In some embodiments, the inorganic filler includes one or more of glass powder, barium glass powder, and zirconium oxide.
[0056] In some embodiments, the additive includes one or more of an inorganic pigment, an antibacterial agent, and an antioxidant. In this way, the performance and appearance of the dental resin material can be improved. Among them, the inorganic pigment can make the resin material have different colors to meet the aesthetic requirements; the antibacterial agent can prevent the growth of bacteria in the oral cavity and reduce the occurrence of caries and periodontitis; the antioxidant can play an antioxidant role and help maintain the color stability of the resin material.
[0057] In some embodiments, the pigment includes one or more of a metal oxide and a metal sulfide. For example, the metal oxide includes at least one of iron oxide and titanium oxide; the metal sulfide includes at least one of cadmium sulfide and zinc sulfide.
[0058] In some embodiments, the antimicrobial agent includes one or more of silver ions and nano-silver, copper ions, fluoride, nano-zinc oxide, and nano-titanium oxide.
[0059] In some embodiments, the antioxidant includes butylated hydroxytoluene (BHT).
[0060] In a second aspect, the present application provides a method for preparing a dental resin material, which can be used to prepare the dental resin material of the first aspect of the present application, and may include the following steps S1-S2:
[0061] S1: soaking the nanocellulose three-dimensional fabric in a mixed solution, wherein the mixed solution contains polymerization monomers of a resin polymer and an initiator;
[0062] S2: hot-pressing the soaked three-dimensional nanocellulose fabric to polymerize the polymerized monomers in situ on the three-dimensional nanocellulose fabric to form a resin polymer, and dispersing the three-dimensional nanocellulose fabric in the resin polymer to obtain a dental resin material.
[0063] The nanocellulose three-dimensional fabric is immersed in a mixed solution containing a polymerizable monomer and an initiator of a resin polymer, so that the polymerizable monomer and the initiator can be fully adsorbed onto the nanocellulose three-dimensional fabric; then the nanocellulose three-dimensional fabric after the immersion treatment is hot-pressed, and under heating conditions, the polymerizable monomer can be in-situ polymerized on the nanocellulose three-dimensional fabric to form a resin polymer, and the resin polymer has a strong polymer network, which can make the nanocellulose three-dimensional fabric evenly distributed in the polymer network; at the same time, under pressure conditions, the polymer network and the nanocellulose three-dimensional fabric dispersed therein can be pressed and formed to obtain a dental resin material, which can effectively enhance the mechanical properties. The preparation method has high repeatability and stability, and is convenient for large-scale production and application.
[0064] In some embodiments, the immersion treatment is carried out at a temperature of 40°C to 60°C.
[0065] In some embodiments, the soaking treatment time is 0.5h~2h, and can be optionally 1h~2h.
[0066] In some embodiments, the negative pressure of the immersion treatment environment is 0.1MPa~1.3MPa, and can be 0.9MPa~1.3MPa. The immersion treatment is carried out under the negative pressure of the environment, so that the three-dimensional nanocellulose fabric can be more fully infiltrated by the polymerized monomer, and the air and bubbles in the fabric can be removed, so that the three-dimensional nanocellulose fabric and the resin polymer can be more fully dispersed and filled, which is beneficial to further improve the strength and mechanical properties of the dental resin material.
[0067] It can be understood that the "negative environmental pressure" mentioned in this application refers to the pressure in the environment being lower than the standard atmospheric pressure.
[0068] In some embodiments, the mixed solution further comprises an inorganic filler and / or an additive.
[0069] In some embodiments, based on the total mass of the polymerization monomer, the initiator, the nanocellulose three-dimensional fabric, the inorganic filler and the additive, the mass percentage of the polymerization monomer is 19% to 30%, the mass percentage of the initiator is 0.5% to 3%, the mass percentage of the nanocellulose three-dimensional fabric is 10% to 30%, the mass percentage of the inorganic filler is 20% to 40%, and the mass percentage of the additive is less than or equal to 5%. The dosage range of each raw material selected above is clear and critical, which can polymerize the polymerization monomer and form a solid polymerization network to wrap the nanocellulose three-dimensional fabric, so that the dental resin material has higher mechanical properties.
[0070] In some embodiments, the initiator includes one or more of benzoyl peroxide (BPO), camphorquinone (CQ) and azobisisobutyronitrile (AIBN). The initiator can initiate a polymerization reaction of the polymerization monomer under certain conditions to form a resin polymer.
[0071] In some embodiments, the mixed liquid comprises a solvent, and the solvent comprises one or more of ethanol, n-propanol and isopropanol.
[0072] In some embodiments, the temperature of the hot pressing is 90°C to 170°C.
[0073] In some embodiments, the hot pressing pressure is 10 MPa to 170 MPa.
[0074] In some embodiments, the heat preservation time of the hot pressing is 1h~4h.
[0075] As a non-limiting example, the preparation process of nanocellulose three-dimensional fabrics may include raw material selection, fiberization treatment, thinning, fiber precision weaving or spinning process to make yarn, post-processing to improve performance and optimize adjustment; weaving and finishing, post-weaving modification to remove impurities, flatten the surface, etc., as follows:
[0076] (1) The nanocellulose raw material is subjected to a fiberization treatment by mechanical shearing, grinding or stretching to make it into a thin and long fiber. It is then further refined using equipment such as a high-pressure homogenizer to increase the fiber length and strength, so that the single fiber diameter reaches 7μm~10μm. Then, a spinning process such as dry spinning is used to make nanocellulose yarn with a diameter of 0.1mm~0.2mm. Finally, post-treatment such as stretching is used to improve the yarn strength and stability. The entire process needs to be optimized and adjusted according to the characteristics of nanocellulose and the performance requirements of the yarn. Among them, the nanocellulose raw material can come from wood, cotton, bacteria, etc., and is prepared by treating wood, cotton, bacteria, etc.
[0077] (2) Use traditional weaving equipment, such as manual weaving needles or mechanical weaving machines, to weave the nanocellulose yarn according to the designed pattern and structure. During weaving, control parameters such as yarn tension, interlacing angle (e.g., the interlacing angle is 90°, and the angle between each layer of plain fabric is 4°) and weaving density (e.g., the line density is 28tex). Manual weaving can be controlled by finger operation, while mechanical weaving adjusts machine parameters to achieve different effects. The woven nanocellulose three-dimensional fabric is subjected to surface silanization treatment to remove impurities such as excess fibers and burrs, and the fabric surface is smoothed and ironed to improve the appearance quality and dimensional stability.
[0078] Optionally, the nanocellulose three-dimensional fabric is formed by stacking multiple layers of plain woven fabric with each layer rotated at an angle of 4° to 5°.
[0079] In some embodiments, the tensile strength of the nanocellulose three-dimensional fabric is 250 MPa to 570 MPa.
[0080] In a third aspect, the present application provides a dental formed body, comprising the dental resin material described in the first aspect of the present application or the dental resin material prepared by the preparation method described in the second aspect of the present application.
[0081] Example
[0082] The following are specific examples, which more specifically describe the contents disclosed in this application, and these examples are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0083] Example 1
[0084] (1) Weigh 28g TEGDMA, 70g UDMA, 2g BISGMA, 0.1g BPO, and 0.1g BHT, add ethanol, and mix by ultrasonic until BPO and BHT are dissolved; then add 20g glass powder, mix and disperse by ultrasonic for 30min to obtain a mixed solution. Put 49g nanocellulose three-dimensional fabric (thickness of about 20mm, length of 30mm, width of 50mm) into the above mixed solution, soak for 2h at an ambient negative pressure of 0.1MPa and a temperature of 50℃, and then take it out.
[0085] (2) The soaked nanocellulose three-dimensional fabric is placed in a mold for hot pressing at a pressure of 170 MPa and a temperature of 140°C. After keeping the temperature for 2 hours, the fabric is naturally cooled to room temperature and demolded to obtain a resin material.
[0086] Example 2
[0087] (1) Weigh 45g TEGDMA, 90g UDMA, 3g BISGMA, 0.1g CQ, and 0.1g antibacterial agent, add ethanol, and mix by ultrasonic until CQ is dissolved; then add 30g glass powder, mix and disperse by ultrasonic for 30min to obtain a mixed solution. Put 59.7g nanocellulose three-dimensional fabric (thickness 22mm, length 35mm, width 50mm) into the above mixed solution, soak for 2h at an ambient negative pressure of 0.1MPa and a temperature of 50℃, and then take it out.
[0088] (2) The soaked nanocellulose three-dimensional fabric is placed in a mold for hot pressing; the pressure is 30 MPa and the temperature is 120°C. After keeping warm for 2 hours, it is naturally cooled to room temperature and demolded to obtain a resin material.
[0089] Example 3
[0090] (1) Weigh 30g TEGDMA, 60g UDMA, and 0.1g BHT, add ethanol, and mix by ultrasonic until BHT is dissolved; then add 25g glass powder, mix and disperse by ultrasonic for 30min to obtain a mixed solution. Put 59g nanocellulose three-dimensional fabric (thickness 22mm, length 35mm, width 51mm) into the mixed solution, soak for 2h at an ambient negative pressure of 0.1MPa and a temperature of 50℃, and then take it out.
[0091] (2) The soaked nanocellulose three-dimensional fabric is placed in a mold for hot pressing; the pressure is 60 MPa and the temperature is 140°C. After keeping the temperature for 1.8 hours, it is naturally cooled to room temperature and demolded to obtain a resin material.
[0092] Example 4
[0093] (1) Weigh 25g TEGDMA, 50g UDMA, 2g BISGMA, 0.1g BPO, and 0.1g BHT, add ethanol, and mix by ultrasonic until BPO and BHT are dissolved; then add 40g glass powder, mix and disperse by ultrasonic for 30min to obtain a mixed solution. Put 45g nanocellulose three-dimensional fabric (thickness 20mm, length 40mm, width 45mm) into the mixed solution, soak for 2h at an ambient negative pressure of 0.1MPa and a temperature of 50℃, and then take it out.
[0094] (2) The soaked nanocellulose three-dimensional fabric is placed in a mold for hot pressing at a pressure of 105 MPa and a temperature of 170°C. After keeping the temperature for 1.3 hours, the fabric is naturally cooled to room temperature and demolded to obtain a resin material.
[0095] Example 5
[0096] (1) Weigh 35g TEGDMA, 45g UDMA, 3g BPO, and 0.4g antibacterial agent, add ethanol, and mix by ultrasonic until BPO is dissolved; then add 45g glass powder, mix and disperse by ultrasonic for 30min to obtain a mixed solution. Put 30g nanocellulose three-dimensional fabric (thickness 20mm, length 38mm, width 48mm) into the above mixed solution, soak for 2h at an ambient negative pressure of 0.1MPa and a temperature of 50℃, and then take it out.
[0097] (2) The soaked nanocellulose three-dimensional fabric is placed in a mold for hot pressing at a pressure of 80 MPa and a temperature of 150°C. After keeping the temperature for 1.7 hours, the fabric is naturally cooled to room temperature and demolded to obtain a resin material.
[0098] Example 6
[0099] (1) Weigh 30g UDMA, 20g BISGMA, 2g CQ, and 0.3g filler, add ethanol, and mix by ultrasonic until CQ is dissolved; then add 30g glass powder, mix and disperse by ultrasonic for 30min to obtain a mixed solution. Put 18g nanocellulose three-dimensional fabric (thickness 20mm, length 42mm, width 46mm) into the above mixed solution, soak for 2h at an ambient negative pressure of 0.1MPa and a temperature of 50℃, and then take it out.
[0100] (2) The soaked nanocellulose three-dimensional fabric is placed in a mold for hot pressing at a pressure of 50 MPa and a temperature of 130°C. After keeping the temperature for 2 hours, the fabric is naturally cooled to room temperature and demolded to obtain a resin material.
[0101] Comparative Example 1
[0102] (1) Weigh 28 g of TEGDMA, 70 g of UDMA, 2 g of BISGMA, 0.1 g of BPO, and 0.1 g of BHT, add ethanol, and mix by ultrasonication until BPO and BHT are dissolved; then add 400 g of glass powder, mix and disperse by ultrasonication for 30 min, and obtain a mixed solution.
[0103] (2) After the mixed liquid is dried for 8 hours, it is placed in a mold for hot pressing; the pressure is 170 MPa and the temperature is 140°C. After keeping the temperature for 2 hours, it is naturally cooled to room temperature and demolded to obtain a resin material.
[0104] Comparative Example 2
[0105] The preparation process is similar to that of Example 1, with the main difference being that in step (1), an equal mass of two-dimensional nanocellulose is used to replace the three-dimensional nanocellulose fabric.
[0106] The resin materials prepared in the above embodiments and comparative examples were subjected to relevant performance tests, and the test results are shown in Table 1 below, wherein "mass percentage of nanocellulose three-dimensional fabric" refers to the mass percentage of nanocellulose three-dimensional fabric in the resin material.
[0107] Among them, the test conditions or test standards for each performance test item are as follows:
[0108] (1) Strength
[0109] According to the three-point bending strength test method in ISO10477, 8 samples were tested in each group of embodiments, and then the average value was taken.
[0110] Table 1
[0111]
[0112] In Table 1, by comparing Examples 1 to 6 with the comparative example, it can be seen that the three-dimensional nanocellulose fabric can improve the bending strength and mechanical properties of the dental resin material; by comparing Examples 1 to 6 with the comparative example 2, it can be seen that compared with the two-dimensional nanocellulose, the three-dimensional nanocellulose fabric has a significantly better improvement effect on the bending strength and mechanical properties.
[0113] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0114] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A dental resin material, characterized in that: The invention comprises a resin polymer and a three-dimensional nanocellulose fabric, wherein the three-dimensional nanocellulose fabric is dispersed in the resin polymer.
2. The dental resin material according to claim 1, characterized in that One or more of the following conditions are met: (1) The mass percentage of the resin polymer in the dental resin material is 10% to 25%, and can be 15% to 25%; (2) The mass percentage of the nanocellulose three-dimensional fabric in the dental resin material is 10% to 35%, and can be 15% to 25%; (3) The length of the nanocellulose three-dimensional fabric is 15 mm to 150 mm, the width is 15 mm to 150 mm, and the thickness is 10 mm to 25 mm.
3. The dental resin material according to claim 1 or 2, characterized in that: The three-dimensional nanocellulose fabric comprises a mesh structure formed by interweaving warp nanocellulose fibers and weft nanocellulose fibers; Optionally, the diameters of the warp nanocellulose fibers and the weft nanocellulose fibers are each independently 1 μm to 10 μm; Optionally, the spacing between two adjacent warp nanocellulose fibers is 20 μm to 40 μm; Optionally, the spacing between two adjacent weft nanocellulose fibers is 20 μm to 40 μm; Optionally, the angle between any two intersecting warp nanocellulose fibers and the weft nanocellulose fibers is 4° to 6°.
4. The dental resin material according to claim 1 or 2, characterized in that: The polymerized monomers of the resin polymer include one or more of methyl methacrylate, bisphenol A glycidyl methacrylate, triethylene glycol dimethacrylate and urethane dimethacrylate.
5. The dental resin material according to claim 1 or 2, characterized in that: The dental resin material further comprises an inorganic filler and / or an additive; Optionally, the mass percentage of the inorganic filler in the dental resin material is 20% to 40%; Optionally, the mass percentage of the additive in the dental resin material is less than or equal to 5%.
6. A method for preparing a dental resin material, characterized in that: include: The nanocellulose three-dimensional fabric is immersed in a mixed solution, wherein the mixed solution contains polymerization monomers of a resin polymer and an initiator; The nanocellulose three-dimensional fabric after the soaking treatment is hot-pressed to make the polymerization monomer in situ polymerize on the nanocellulose three-dimensional fabric to form a resin polymer, and the nanocellulose three-dimensional fabric is dispersed in the resin polymer to prepare a dental resin material.
7. The preparation method according to claim 6, characterized in that: One or more of the following conditions are met: (1) The immersion temperature is 40°C to 60°C; (2) The soaking time is 0.5h~2h; (3) The negative pressure of the environment during the immersion treatment is 0.1 MPa to 1.3 MPa.
8. The preparation method according to claim 6 or 7, characterized in that: The mixed solution further comprises an inorganic filler and / or an additive; Optionally, based on the total mass of the polymerization monomer, the initiator, the nanocellulose three-dimensional fabric, the inorganic filler and the additive, the mass percentage of the polymerization monomer is 19% to 30%, the mass percentage of the initiator is 0.5% to 3%, the mass percentage of the nanocellulose three-dimensional fabric is 10% to 30%, the mass percentage of the inorganic filler is 20% to 40%, and the mass percentage of the additive is less than or equal to 5%.
9. The preparation method according to claim 6 or 7, characterized in that: One or more of the following conditions are met: (1) The temperature of the hot pressing is 90°C to 170°C; (2) The hot pressing pressure is 10MPa~170MPa; (3) The heat preservation time of the hot pressing is 1h~4h.
10. A dental molded body, characterized in that: The present invention comprises the dental resin material according to any one of claims 1 to 5 or the dental resin material prepared by the preparation method according to any one of claims 6 to 9.